Strength Of Profitability As Moderating Tax And Corporate Governance On Firm Value - Mila Sari; Anita Ade Rahma (Information Technology and Science (ITScience), 2022)
This study aims to determine and estimate the effect of tax planning, managerial ownership, and foreign commissioners on firm value with profitability as a moderating variable in manufacturing companies listed on the Indonesian stock exchange. Based on the results of partial hypothesis testing, it can be concluded that tax planning has no effect on firm value. Managerial ownership has an effect on firm value. The foreign board of commissioners has no effect on the value of the company. In tax planning, managerial ownership, and foreign commissioners simultaneously affect the value of the company. Tax planning has no effect on firm value with profitability as a moderation. Managerial ownership has an effect on firm value with profitability as moderating. Foreign board of commissioners affect the value of the company with profitability as moderating. Profitability has an effect on firm value. The amount of managerial ownership in a company has a very important role in increasing the value of the company. This is of course due to a greater attachment to management and care for the sustainability and progress of the company.